Murder for the halibut / Liz Lipperman - Lipperman, Liz, 1947- (Lipperman, Liz, 1947- Clueless cook mystery., 2012)
"Tempted by the offer of a free Caribbean cruise, Jordan accepts a spot as a judge in a week-long big-time cooking competition aboard the Carnation Queen. She just better hope no one finds out that her famous palate is far from refined. But there are bigger fish to fry when arrogant chef Stefano Mancini falls face first into his signature halibut dish during the first event. While evidence suggests that the handsome Italian chef's death was an accident, Jordan thinks otherwise. But she'll have to keep her wits about her--and the sea sickness pills handy--if she's going to solve this one ..."--Page 4 of cover.